The Influence of Professional Education and Work Motivation on The Performance of State Elementary School Teachers - Alfianita, Riani; Karnati, Neti; Supadi, Supadi; Ifnuari, Moh Reza (Journal of Education Reseach and Evaluation, 2022)
Improving the quality of education is continually strived for by every school through teacher performance. Improving teacher performance is influenced by many factors, including the development of the teaching profession and work motivation. The purpose of this study is to describe the positive influence of professional education and motivation on performance. This research was conducted on elementary school teachers with 210 Civil Servant teachers who have attended professional education and teach at public elementary schools in the area. The time used during research activities is four months. The data analysis used is the structural equation model (SEM). By using the AMOS software. The findings of the study that there is a direct positive effect of professional education on performance. Work motivation has a direct positive effect on teacher performance significantly. Professional education has a positive effect on motivation. For this reason, the success of the implementation of teacher professional education, which is the main factor in motivating teachers, needs to be maintained and controlled by conducting scheduled evaluations.